Comparison of Pre-Mixed Human Insulin with Insulin Analog in Diabetic Control at Tertiary Care Hospital - Syed Fahad Ul Hassan; Muhammad Zahid Hussain; Ishtiaq Munir Janjua; Hassan Salim; Saadia Javed; Muhammad Tahir Younas (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the effect of pre-mixed human insulin with insulin analogue in diabetic control among type-2 Diabetes mellitus patients at tertiary care hospital.